If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 * 0 + -3 * -4 = 11 Multiply 7 * 0 0 + -3 * -4 = 11 Anything times zero is zero. 0 + -3 * -4 = 11 Multiply -3 * -4 0 + 12 = 11 Combine like terms: 0 + 12 = 12 12 = 11 Solving 12 = 11 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (3x-7)2+5(2x+1)(x-2)=-x^2-[-(3x+1)] | | x-15=8x+6 | | -2(w+4)=w-5+3(4w+1) | | 3xty=32 | | 5.25-0.75a=5.25+0.75a | | 5.25-0.75a=5.25+0.75 | | 5*-4+2*-6=-1 | | -3x-3(6x+6)=-18+4x | | 7x^2+28x+63=0 | | 5*1+2*-3=-1 | | 17-5m=50+3m | | 14y^2-23y+9= | | 5*2+2*8=-1 | | -12x+14=12x-82 | | -4y-1=21.75 | | 0.8x+4=0 | | .40C+(.50)(500-C)=220.00 | | 55=75+1-25 | | -3.8n+4=4.4n-37 | | 5*-3+2*7=-1 | | 22+2x=x | | -96=-4(6+3x) | | 5x=49 | | 6y-12x=-24 | | (n+1)(n-9)=0 | | 90-22+2x=x | | 14+2n=5n-6 | | 32=3.2d | | x-0.30x=105 | | 2(g-h)=b-4 | | 6(x-8)=5(x+8) | | 5(x+5)+2x-3=54 |